2009
DOI: 10.17159/2413-3051/2009/v20i4a3307
|View full text |Cite
|
Sign up to set email alerts
|

Determination of regional emission factors for the power sector in Southern Africa

Abstract: The generation of power within Southern Africa is reviewed. A study is described in which the emission factors for CO 2 and NO x were determined experimentally across a wide range of power stations and technologies, and compared to the IPCC default factors. It was found that the CO 2 emission factors tended to be at the upper end of the IPCC default range, whereas the NOx emission factors were generally below the low end. The results from South Africa tend to dominate the regional picture at present, but this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Data for greenhouse gas emissions for the coal supply included the emissions from coal mining in South Africa, which was taken from Zhou et al . [ 48 ], and the emissions from the transport of coal were extracted from the GREET (The Greenhouse Gases, Regulated Emissions, and Energy Use in Transportation) [ 49 ] database (Argonne National Laboratory, Chicago, USA). The ethanol production was assumed to replace an equivalent amount of gasoline [ 50 ], and the emissions resulting from that amount of gasoline (specific CO 2(eq) taken from GREET [ 49 ]) was subtracted from the system emissions, as per the substitute method [ 43 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data for greenhouse gas emissions for the coal supply included the emissions from coal mining in South Africa, which was taken from Zhou et al . [ 48 ], and the emissions from the transport of coal were extracted from the GREET (The Greenhouse Gases, Regulated Emissions, and Energy Use in Transportation) [ 49 ] database (Argonne National Laboratory, Chicago, USA). The ethanol production was assumed to replace an equivalent amount of gasoline [ 50 ], and the emissions resulting from that amount of gasoline (specific CO 2(eq) taken from GREET [ 49 ]) was subtracted from the system emissions, as per the substitute method [ 43 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the past, regional CO 2 and NO x emission factors for the power sector in Southern Africa were determined both theoretically and from continuous in-stack measurements for comparison to the Intergovernmental Panel on Climate Change (IPCC) default emission factors (Zhou et al 2009). It was found that Southern African CO 2 emission factors were on the upper end of the IPCC default emission range whereas NO 2 emission factors were below the low end of the range.…”
Section: Introductionmentioning
confidence: 99%